Subsidies and exports in Germany first evidence from enterprise panel data - Sourafel Girma; Holger Görg; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2009)
We use newly available representative panel data for manufacturing enterprises in West and East Germany to investigate the link between production-related subsidies and exports. We document that only a small fraction of enterprises is subsidized, and that exports and subsidies are positively related. Using a matching approach to investigate the causal effect of subsidies on export activities we find no impact of subsidies on the probability to start exporting, and only weak evidence for an impact of subsidies on the share of exports in total sales in West Germany but no evidence in East Germany.
Keywords: F13; F14; H29; 330; Subsidies; export; Germany; enterprise panel data; Industriesubvention; Verarbeitendes Gewerbe; Export; Exportindustrie; Deutschland